2018
DOI: 10.1016/j.brainres.2018.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Kisspeptin system in ovariectomized mice: Estradiol and progesterone regulation

Abstract: The kisspeptin system is clustered in two main groups of cell bodies (the periventricular region, RP3V and the arcuate nucleus, ARC) that send fibers mainly to the GnRH neurons and in a few other locations, including the paraventricular nucleus, PVN. In physiological conditions, gonadal hormones modulate the kisspeptin system with expression changes according to different phases of the estrous cycle: the highest being in estrus phase in RP3V and PVN (positive feedback), and in ARC during the diestrus phase (ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 42 publications
3
15
1
Order By: Relevance
“…Due to differences in the immunostaining, the range of the Environmental Health Perspectives 107011-3 127(10) October 2019 threshold was individually adjusted for each section. In line with our previous studies (Marraudino et al 2018;Panzica et al 2011), the Kp-IR cell bodies were clearly visible only in the RP3V, whereas they were not clearly discernible in the ARC due to dense fiber accumulation. Therefore, the number of Kp-IR cell bodies was measured only in the RP3V, by the Cell Counter plugin of ImageJ, and expressed as total number of cells in the reference area.…”
Section: Kisspeptin Immunohistochemistry and Quantitative Analysissupporting
confidence: 92%
See 2 more Smart Citations
“…Due to differences in the immunostaining, the range of the Environmental Health Perspectives 107011-3 127(10) October 2019 threshold was individually adjusted for each section. In line with our previous studies (Marraudino et al 2018;Panzica et al 2011), the Kp-IR cell bodies were clearly visible only in the RP3V, whereas they were not clearly discernible in the ARC due to dense fiber accumulation. Therefore, the number of Kp-IR cell bodies was measured only in the RP3V, by the Cell Counter plugin of ImageJ, and expressed as total number of cells in the reference area.…”
Section: Kisspeptin Immunohistochemistry and Quantitative Analysissupporting
confidence: 92%
“…In fact, quantitative analyses by ISH revealed that such a suppression of Kiss1 was persistently detectable from the infantile period to the pubertal stage. It is well accepted that ARC Kiss1 neurons are sensitive to the inhibitory action of sex steroids, including estrogens, on Kiss1 expression (Marraudino et al 2018;Pinilla et al 2012;Smith et al 2005aSmith et al , 2005b. Although the effects of perinatal BPA are compatible with this action, it must be stressed that such an effect was intergenerational given that BPA was administered to the mothers (not to the pups) during a restricted time window, therefore suggesting potential developmental or organizing actions of this EDC on the maturation of the population of ARC Kiss1 neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 The underlying mechanism may involve progesterone signaling. 18 "Present results indicate that this differential sensitivity is probably established early during the development Girls have been entering puberty at increasingly younger average ages since the 1800s, in no small part because health and nutrition have improved over time. 20 Today, environmental factors, perhaps including endocrine disruptors, may influence the onset of puberty in complex ways.…”
mentioning
confidence: 68%
“… 17 The underlying mechanism may involve progesterone signaling. 18 “Present results indicate that this differential sensitivity is probably established early during the development and this may explain the different effects of BPA on the two hypothalamic nuclei,” Panzica says.…”
mentioning
confidence: 82%